CARPAL BONE (CAPITATE) STUDY IN CADAVERS OF VIDARBHA REGION - DR. RAJESH DEHANKAR; DR. UJJWALA BHAKARE; DR. D. D. KSHEERSAGAR (International Journal of Pharma and Bio Sciences, 2013)
Various features of human identity can be determined by the study of human skeleton. Bone age development is one of the significant indicators depicting the growth status in children. The present study is done in Vidarbha region of Maharashtra where climatic conditions, nutritional status Socio-economic status and pattern of diseases are different from other regions. Measurements of even smaller bones i.e carpal bones like capitates are helpful in determining the age, sex and stature of an individual. Aim of the study is to assess different measurements of human capitate for assessment of age, sex and bilateral asymmetry. The study is carried out in the department of Anatomy NKPSIMS, Nagpur. 60 fully ossified capitates belonging to dissection hall cadavers of both sexes and known age are included in the study. Measurements were taken using vernier calipers and spreading calipers. To analyze various parameters statistical methods are used to find out mean, SD, Coefficient of variation, & SE of mean. Sex differentiation is also done by using identification points on the bones. Identification points are the limiting points of the range for males and females. The parameters were compared with the work done by other researchers and it was concluded that sex determination can be done with the help of demarking points also weight and length are best parameters for sex determination.